THE EFFECT OF EMOTIONAL INTELLIGENCE COUNSELING ON ELEMENTARY SCHOOL STUDENTS’ SELF-CONTROL IN FACING CONFLICTS - Muhammad Syahrul; Rinovian Rais; Yuli Yanti; Rusyati Prihatin; Asni Asni (International Journal of Educatio Elementaria and Psychologia, 2025)
Emotional intelligence plays a crucial role in fostering students' ability to manage emotions and navigate interpersonal conflicts effectively. This study examines the impact of emotional intelligence counseling on enhancing self-control among elementary school students when dealing with conflicts. The research aimed to identify the effectiveness of a structured counseling intervention in improving students' emotional regulation and conflict resolution skills. A quasi-experimental method with a pre-test and post-test control group design was employed. The sample consisted of 60 elementary school students selected through purposive sampling, divided equally into experimental and control groups. Data were collected using self-control questionnaires, conflict observation sheets, and structured interviews. The results indicated a significant improvement in self-control among students who participated in emotional intelligence counseling compared to those in the control group. Participants demonstrated enhanced emotional regulation, reduced impulsive behaviors, and improved ability to resolve conflicts constructively. The findings suggest that integrating emotional intelligence counseling into school programs effectively supports the development of students’ social-emotional skills.